2012
DOI: 10.1590/s1516-14392012005000069
|View full text |Cite
|
Sign up to set email alerts
|

XRD, AFM, IR and TGA study of nanostructured hydroxyapatite

Abstract: In this work, the synthetic hydroxyapatite (HAP) was studied using different preparation routes to decrease the crystal size and to study the temperature effect on the HAP nano-sized hydroxyapatite crystallization. X-ray diffraction (XRD) analysis indicated that all samples were composed by crystalline and amorphous phases . The sample with greater quantity of amorphous phase (40% of total mass) was studied. The nano-sized hydroxyapatite powder was heated and studied at 300, 500, 700, 900 and 1150 °C. All samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 19 publications
5
27
0
Order By: Relevance
“…This demonstrated that there were chemical interactions between β-TCP material and SBF solution. These interactions would lead to the commute of β-TCP (beta-tricalcium phosphate) to HA (hydroxyapatite) versus time and continued until β-TCP completely transformed into HA (Mirta et al 2012). Obtained result confirmed the bioactivity of β-TCP. )…”
Section: Physico-chemical Characterizationsupporting
confidence: 53%
See 1 more Smart Citation
“…This demonstrated that there were chemical interactions between β-TCP material and SBF solution. These interactions would lead to the commute of β-TCP (beta-tricalcium phosphate) to HA (hydroxyapatite) versus time and continued until β-TCP completely transformed into HA (Mirta et al 2012). Obtained result confirmed the bioactivity of β-TCP. )…”
Section: Physico-chemical Characterizationsupporting
confidence: 53%
“…Obtained result confirmed the bioactivity of β-TCP. ) (Mirta et al 2012). That demonstrated that after 5 days in SBF solution, β-TCP had transferred one part into HA.…”
Section: Physico-chemical Characterizationmentioning
confidence: 96%
“…[20][21][22] The weak shoulder at 964 cm −1 and the broadband at 1033 cm −1 with shoulder at 1093 cm −1 correspond to the vibrational modes of stretch ν 1 and ν 3 of the phosphate group (PO 4 3− ), while the shoulder at 474 cm −1 and the strong bands at 566 and 601 cm −1 indicate the presence of the vibrational modes ν 2 and ν 4 of flexion of this same group. 22 The bands related to the stretching of the hydroxyl group (OH − ) can be observed at 3575 and 630 cm −1 , 21 and they gradually decrease while the Sr concentration increases. According to Frasnelli et al, 12 the deformation of the HA unit cell in the c-axis can lead to a limitation in spatial density of the bonds of the OH − .…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 97%
“…An increase in calcination temperature results in narrowing and sharpening of diffraction peaks as an indicator of raised crystallinity and an increase in crystal/grain size. 49 Further increase in temperature leads to dehydroxylation as a result of the separation of structural OH − group with corresponding changes in absorption bands at 630 and 3572 cm −1 . 48 Furthermore, the thermal treatment can also induce non-structural and structural changes in the phase composition of biomaterials that can be traced as alterations in FTIR absorption bands.…”
Section: Modification Of Calcination Parameters and Their Importancementioning
confidence: 99%